Synergistic DNA‐ and Protein‐Based Recognition Promote an RNA‐Templated Bio‐orthogonal Reaction. Issue 40 (1st June 2021) - McLoughlin, Niall M.; Kuepper, Arne; Neubacher, Saskia; Grossmann, Tom N.
Abstract: Biomolecular assemblies composed of proteins and oligonucleotides play a central role in biological processes. While in nature, oligonucleotides and proteins usually assemble via non‐covalent interactions, synthetic conjugates have been developed which covalently link both modalities. The resulting peptide‐oligonucleotide conjugates have facilitated novel biological applications as well as the design of functional supramolecular systems and materials. However, despite the importance of concerted protein/oligonucleotide recognition in nature, conjugation approaches have barely utilized the synergistic recognition abilities of such complexes. Herein, the structure‐based design of peptide‐DNA conjugates that bind RNA through Watson‐Crick base pairing combined with peptide‐mediated major groove recognition is reported. Two distinct conjugate families with tunable binding characteristics have been designed to adjacently bind a particular RNA sequence. In the resulting ternary complex, their peptide elements are located in proximity, a feature that was used to enable an RNA‐templated click reaction. The introduced structure‐based design approach opens the door to novel functional biomolecular assemblies. Abstract : DNA, Protein, RNA : The structure‐based design of biomolecular conjugates composed of protein and DNA fragments that synergistically bind RNA via Watson‐Crick base pairing and peptide‐mediated major groove recognition is reported. Two distinct conjugate families with tunable binding characteristics were designed whereby two conjugates can simultaneously assemble on a single RNA scaffold. Through ternary complex formation, the peptide elements of each conjugate are drawn into close proximity, and this feature was exploited to enable an RNA‐templated, double click reaction.